2015
DOI: 10.1038/ncomms7116
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected role of polyubiquitin chains in the formation of fibrillar aggregates

Abstract: Ubiquitin is known to be one of the most soluble and stably folded intracellular proteins, but it is often found in inclusion bodies associated with various diseases including neurodegenerative disorders and cancer. To gain insight into this contradictory behaviour, we have examined the physicochemical properties of ubiquitin and its polymeric chains that lead to aggregate formation. We find that the folding stability of ubiquitin chains unexpectedly decreases with increasing chain length, resulting in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 51 publications
3
82
0
1
Order By: Relevance
“…Our data support the idea that, after poly-ubiquitinated cargo is recognized by p62, this causes the formation of shorter and less compact helical filaments than those formed by p62 alone (Figure 6). At the current state of research, it is also possible to envision that at low concentrations poly-ubiquitin chains actively crosslink p62 filaments (Morimoto et al, 2015), whereas at molar excess poly-ubiquitin chains disassemble p62 filaments. Moreover, membrane-enwrapped p62 bodies can also enter the autophagosomal pathway without enclosing additional cytoplasmic material to be degraded (Bjørkøy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the idea that, after poly-ubiquitinated cargo is recognized by p62, this causes the formation of shorter and less compact helical filaments than those formed by p62 alone (Figure 6). At the current state of research, it is also possible to envision that at low concentrations poly-ubiquitin chains actively crosslink p62 filaments (Morimoto et al, 2015), whereas at molar excess poly-ubiquitin chains disassemble p62 filaments. Moreover, membrane-enwrapped p62 bodies can also enter the autophagosomal pathway without enclosing additional cytoplasmic material to be degraded (Bjørkøy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the role of shuttling factors and proteasomal receptors in recognizing ubiquitinated substrates, autophagy relies on its own arsenal of autophagy receptors to recognize intracellular ubiquitinated aggregates (p62, NBR1, OPTN, TOLLIP) [32][33][34][35][36], bacteria (p62, OPTN, NDP52) [37][38][39], peroxisomes (NBR1) [40], mitochondria (OPTN, NDP52, Tax1BP1) [41][42][43], zymogen particles (p62) [16], proteasome (RPN10) [24], midbody (p62, NBR1) [15,44], or nucleic acids (p62, NDP52) [18,45] (Table 1), and link the material to autophagosomal membranes. Notably, the capacity of ubiquitinated proteins to form aggregates, and thus become autophagy substrates, has been shown to depend on Ub chain length [46]. It is conceivable that Ub linkage type may also affect protein aggregation and/or clearance by autophagy [47], but genetic disruption of the essential autophagy genes Atg5 or Atg7 results in the accumulation of Ub chains of different topology, indicating that any Ub linkage type could serve as a degradation signal for autophagy [48].…”
Section: Regulation Of Selective Autophagy By the Ub Systemmentioning
confidence: 99%
“…We previously observed that the thermal unfolding of FKBP12 is reversible; in contrast, N-terminally ubiquitylated FKBP12 displays an irreversible transition7. Similarly, ubiquitin loses its thermal folding reversibility by polymerization or conjugation to other proteins7; thus, we considered whether FKBP12 in its ubiquitylated form is simply entrapped by insoluble ubiquitin aggregates during heat denaturation, or whether it loses its own folding reversibility alongside ubiquitin.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent molecular dynamics analysis showed that ubiquitylation might be capable of causing partial unfolding of substrate proteins6. Furthermore, we previously observed a decrease in the thermodynamic stability of ubiquitin itself due to polymerization7. We therefore hypothesized that the fold of ubiquitylated proteins might be destabilized via a molecular mechanism similar to that observed for polyubiquitin chains.…”
mentioning
confidence: 81%